2013
DOI: 10.1074/jbc.m112.420521
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Arenaviral Nucleoproteins with Triphosphate dsRNA Reveal a Unique Mechanism of Immune Suppression

Abstract: Background: Arenaviral nucleoproteins play a critical role in innate immune suppression.Results: Structures of Lassa nucleoprotein in complex with triphosphate dsRNA and Tacaribe virus nucleoprotein have been determined.Conclusion: Both Lassa and Tacaribe nucleoproteins can strongly inhibit IFN-β production by degrading immune-stimulatory dsRNA.Significance: A unique immune suppression mode of arenaviral nucleoproteins has been revealed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
140
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(152 citation statements)
references
References 30 publications
8
140
0
2
Order By: Relevance
“…We show that residues 389 and 392 in the active site of the exonuclease domain of NP or nearby strongly affect IFN production by APC (19). Other investigators have confirmed that residue 389 is mandatory for functional exonuclease activity of NP (7,9). In addition to the inhibition of primary responses in LASV-infected cells, an early blockade of type I IFN production prevents subsequent transcription of IFN-stimulated genes (ISG), including some encoding mediators of NK cell activation.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…We show that residues 389 and 392 in the active site of the exonuclease domain of NP or nearby strongly affect IFN production by APC (19). Other investigators have confirmed that residue 389 is mandatory for functional exonuclease activity of NP (7,9). In addition to the inhibition of primary responses in LASV-infected cells, an early blockade of type I IFN production prevents subsequent transcription of IFN-stimulated genes (ISG), including some encoding mediators of NK cell activation.…”
Section: Discussionmentioning
confidence: 63%
“…LASV and other arenaviruses suppress IFN production via a unique exonuclease activity of NP (7)(8)(9). This function allows NP to digest viral dsRNA substrates generally sensed by retinoic acidinducible gene I (RIG-I).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RNP not only serves as a template for viral RNA replication and transcription by the cognate viral RNA-dependent RNA polymerase (RdRp), but also protects the viral genome from ribonucleases and helps to avoid alerting the host innate immune response (Qi et al 2010;Jiang et al 2013). Although the nucleoproteins have similar functions in different families of negative-sense RNA viruses, their structures seem to be very variable, as exemplified by our previous publication reporting the crystal structure of the SBV N protein ).…”
Section: Discussionmentioning
confidence: 99%
“…This inhibition is due to the 3=-5= exonuclease (ExoN) function of the NP, which digests free double-stranded RNA. This prevents RNA recognition by retinoic acid-inducible gene I (RIG-I), a pattern recognition receptor (PRR) that recognizes double-stranded RNA (12)(13)(14)(15). We used our reverse-genetics system for LASV to generate a recombinant wild-type LASV (LASV-WT) and another LASV, LASV-ExoN, with two mutations (D389A and G392A) affecting the NP (16).…”
Section: Assa Virus (Lasv) Is An Oldmentioning
confidence: 99%